PENGARUH CASH RATIO, DEBT TO EQUITY RATIO, DAN EARNING PER SHARE TERHADAP CASH DIVIDEND PADA PERUSAHAAN FOOD AND BEVERAGES YANG TERDAFTAR DI BURSA EFEK INDONESIA SELAMA PERIODE 2005-2010 - Dewanti, Made Ayu Lisna; Sudiartha, Gede Merta (E-Jurnal Manajemen; Vol 2 No 2 (2013), 2013)
ABSTRACT This study has the objective to determine the effect of the cash ratio, debt to equity ratio, and earnings per share of the cash dividend on the company's food and beverages. The data used in this study are secondary data from company financial statements food and beverages in the IDX period 2005-2010. Sampling method using purposive sampling. Results of analysis of this study showed only CR variables that affect cash dividend, while the DER and the EPS does not affect the cash dividend on the Stock Exchange. Keywords : Cash Dividen d , Cash Ratio , Debt to Equity Ratio , Earning per Share